Between Sharia and State: Fatwa Authority and Pandemic Responses in Indonesia, Turkey, and Morocco - Taufiq, Muhammad; Faiz, Muhammad Fauzinudin; Ravaşdeh, Ziyad (Shariah Faculty UIN Maulana Malik Ibrahim Malang, 2025)
The reactions of Muslim communities to the COVID-19 pandemic highlight the importance of the relationship between Sharia and the state in developing a fiqh of mitigation for future pandemics. Muslim-majority countries faced significant challenges in balancing health protocols with religious obligations, such as mosque closures, the suspension of Ramadan and Hajj rituals, and debates over the halal status of vaccines. In this context, fatwa authorities played a crucial role in mediating between state policies and the religious sensitivities of the public. This study explores the Sharia–state relations through the intersection of Islamic jurisprudence (fiqh), fatwa authority, and pandemic responses in Indonesia, Turkey, and Morocco. Each country exemplifies a distinct relationship between state and religious authority, influencing how pandemic mitigation strategies are received and implemented. Utilising empirical legal methods and the fiqh of mitigation based on the principles of maqāṣid al-sharī‘a, particularly ḥifẓ al-nafs (preservation of life), maslahah (public interest), and saddu al-dzārī‘ah (preventive measures), this study highlights how religious decrees (fatwas) align with or diverge from public health regulations. The findings reveal that Sharia-state relations are crucial in building the fiqh of mitigation, public compliance, and state–religion cooperation. The study advocates for institutionalising a fiqh of mitigation to prepare Muslim societies for future pandemic crises through a balanced approach that integrates Sharia principles and public health governance.